Pergamon, Türkei. Pergamon. Die Arbeiten des Jahres 2020 - Pirson, Felix (e-Forschungsberichte des DAI, 2021)
Due to the pandemic, a hygiene concept had to be implemented before the work schedule of the Pergamon excavation and the associated survey projects planned for 2020 could be carried out at least to a limited extent. On the northern slope of the city hill of Pergamon, a Hellenistic-Roman burial precinct was excavated and has yielded important new insights. The focus of the work, however, was on continuing the new programme »The Transformation of the Pergamon Micro-region between Hellenism and the Roman Empire« (TransPergMikro). Architectural remains were documented in the amphitheatre of Pergamon and, for the first time, also in the Roman theatre on the hill Musalla Mezarlığı. The survey in the surroundings of the Asklepieion concentrated on quarries and burial sites, while the survey in the Micro-region made the valley of Geyikli northwest of Pergamon with a Roman thermal complex the starting point of this year‘s investigations. The fieldwork at the site of ancient pottery-production at Çandarlı (Pitane) could be completed, while the team of German-Turkish physical geographers continued the exploration of sediment formations at various locations in the western Bakırçay plain.